The role of substrate bias and nitrogen doping on the structural evolution and local elastic modulus of diamond-like carbon films. (31st March 2017) - Polaki, S R; Ganesan, K; Srivastava, S K; Kamruddin, M; Tyagi, A K
Abstract: Diamond-like carbon (DLC) films are synthesized on Si using plasma enhanced chemical vapor deposition. The role of substrate bias and nitrogen doping on the structural evolution and local elastic modulus of DLC films are systematically investigated. Raman spectroscopic studies reveal that the amount of graphitic C  =  C sp 2 bonding increases with substrate bias and nitrogen doping. The density and hydrogen concentration in the films are found to vary from 0.7 to 2.2 g cm −3 and 16 to 38 atomic %, respectively, depending upon the substrate bias and nitrogen concentration in the DLC films. Atomic force acoustic microscopy (AFAM) analysis shows a direct correlation between the local elastic modulus and the structural properties estimated by Raman spectroscopy, Rutherford back scattering and elastic recoil detection analysis. AFAM analysis further confirms the evolution of soft second phases at high substrate biases (⩾  −150 V) in undoped DLC films. Further, N doping leads to the formation of such soft second phases in DLC films even at a lower substrate bias of  −100 V. The AFAM studies provide direct microscopic evidence for the 'sub-implantation growth model', which predicts the formation of graphitic second phases in the DLC matrix at high substrate biases.